2019
DOI: 10.1016/j.omtm.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Exosome Enveloped-AAV Spreading by Endomicroscopy Approach: A New Tool for Gene Delivery in the Brain

Abstract: Exosomes represent a strategy for optimizing the adeno-associated virus (AAV) toward the development of novel therapeutic options for neurodegenerative disorders. However, in vivo spreading of exosomes and AAVs after intracerebral administration is poorly understood. This study provides an assessment and comparison of the spreading into the brain of exosome-enveloped AAVs (exo-AAVs) or unassociated AAVs (std-AAVs) through in vivo optical imaging techniques like pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 56 publications
(58 reference statements)
2
20
0
Order By: Relevance
“…In contrast to our study using AAV1, one of the lentivirus studies reported low tropisms for astrocytes using the mPGK promoter [ 61 ]. A study that used the human PGK promoter with AAV serotypes 6, 9, and rh10 reported predominant expression in neurons and a limited number of astrocytes and oligodendrocytes [ 62 , 63 ]. In addition, we found that the mPGK promoter is a strong promoter in terms of transgene expression in the sensorimotor cortex; mPGK promoter was superior over the hCMV and sCAG promoters.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study using AAV1, one of the lentivirus studies reported low tropisms for astrocytes using the mPGK promoter [ 61 ]. A study that used the human PGK promoter with AAV serotypes 6, 9, and rh10 reported predominant expression in neurons and a limited number of astrocytes and oligodendrocytes [ 62 , 63 ]. In addition, we found that the mPGK promoter is a strong promoter in terms of transgene expression in the sensorimotor cortex; mPGK promoter was superior over the hCMV and sCAG promoters.…”
Section: Discussionmentioning
confidence: 99%
“…This can be accomplished by AAV-driven cre-recombinase expression within defined brain regions using cell type-selective promoters in mice that are conditional knockouts for proteins of interest or in mice transduced with other cre-recombinase-dependent vectors 85, 86, 87. Also, mechanistic changes downstream of neuronal activation or silencing are now achievable with AAVs that can control endosome trafficking via light, which allows for general control of removal or reinsertion of proteins such as membrane signaling or adhesion molecules at specific sites 88 . Also, recently the machinery required for CRISPR, the directed gene editing technique, have been packaged into AAVs to perform site-specific gene editing in neurons of interest to perform gain- or loss-of-function mutations as well as gene editing in real time to determine the effects of genetic alteration on circuit function 89, 90, 91…”
Section: Introductionmentioning
confidence: 99%
“…Other studies based on exo-AAVs have reported an improvement of transduction profiles in different AAV serotype in vitro and in vivo conditions [72,82]. While György et al [83] document that exo-AAV1 (the number denotes the capsid serotype) is a potent carrier of transgenes into cochlear and vestibular hair cells both in vitro and in vivo, Orefice et al [84] reported an enhancement of the transgene expression resulting from two different AAV serotypes (AAV6 and AAV9) enveloped with exosomes restricted mainly to neurons ( Figure 1) and oligodendrocytes ( Figure 2). Clinical studies have reported that the trigger of neurodegenerative diseases can arise in a focus of genetically altered cells [72] and spread from one region of the CNS to another.…”
Section: Vexosomes: a Novel Gene Delivery Systemmentioning
confidence: 99%
“…In this context, the study by Orefice et al revealed an interesting feature that might be imported to better optimize the exo-AVV like a valid therapeutic gene delivery. The continual expansion of miniaturized optical fiber-based endoscopes enabled real-time imaging to track the exo-AAV spread into the brain, showing it more widespread in the contralateral hemisphere than standard AAVs after intracerebral injections [84]. This study, added with previous studies conducted in the last few years, highlights the potential of using exo-AAVs for gene delivery, particularly to address the issue of diffusion limitations associated with large fragments of DNA to reach CNS cells far from the injection site.…”
Section: Vexosomes: a Novel Gene Delivery Systemmentioning
confidence: 99%